ADVANTAGE AND DISADVANTAGE THE USE OF E-LEARNING IN HIGHER EDUCATION: ACADEMIC STAFF PERSPECTIVE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In the studying of some contributions studied by different researchers and institutions on the concept of e-learning, especially its use in teaching and learning in the institutions of higher educational, this study provides a scholarly background for the study. This study begins with definitions of e-learning provided by various scholars, the purpose that e-learning plays in higher educational institutions in the process of teaching and learning, as well as the benefits and drawbacks of electronic learning.The primary goal of this study is to shed light on the various advantages, disadvantages, and difficulties of e-learning so that students and researchers can better understand this technology. Additionally, this research will demonstrate the value of e-learning tools like Google Classroom and Moodle for information sharing in higher education. By analyzing the findings, this research aims to shed light on some of the disadvantages and benefits of using the systems of e-learning only in emergency situations rather than as a substitute for conventional higher education.